A novel multi-filament winding technique for type III composite pressure vessel: From CFRP cross-undulation concept to structural performance validation. (26th May 2023) - Zhao, Xiaodong; Liang, Jianguo; Liu, Jianglin; Feng, Jun; Qin, Zelin; Gao, Haifeng; Guo, Zhangxin; Jia, Zhaotun
Abstract: Filament winding (FW) technique determines the production efficiency of wound products and the bearing capacity of composite layers, so the development and innovation of winding technique and equipment have become the focus of scientific researchers. This paper analyzes the influence of fiber crossing on the composite layers in the single filament winding (SFW) technique, proposes a multi-filament winding (MFW) technique. Firstly, the constitutive model of fiber cross region is constructed from mesoscopic scale, and the influence of this phenomenon on the design of composite layers is illustrated using netting theory. Then, the MFW technique is designed and developed, and the three-point bending test of CFRP is carried out with digital image correlation (DIC) technology, indicating that the MFW technique exhibits superior flexural strength of 483.71 MPa. Finally, a 35 MPa type III vessel is taken as the object for comparative numerical simulation, the results show the stress adopting the MFW technique in the dome section is reduced by 1418 MPa, and is smaller and more evenly distributed in the cylinder section. The MFW technique takes full advantage of the CFRP properties, improves the pressure bearing capacity of composite layers, meets the American DOT-CFFC standard requirements, and reduces the carbon fiber usage. The lightweight design of high-pressure hydrogen storage vessels is realized with a novel idea, and the winding efficiency is greatly improved compared with SFW technique. Graphical abstract: Image 1 Highlights: The disadvantages of traditional filament winding technique are revealed. Multi-filament winding (MFW) technique is proposed innovatively. The theory of variable yarn thickness and variable yarn width is developed. The composite layers with MFW technique have a better bearing performance. MFW technique realizes lighter and more efficient manufacturing of pressure vessels.